2019
DOI: 10.1159/000503692
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of [18F]FFMZ and [18F]FDG PET Studies in the Localization of Seizure Onset Zone in Drug-Resistant Temporal Lobe Epilepsy

Abstract: <b><i>Background:</i></b> Positron emission tomography (PET) imaging in epilepsy is an in vivo technique that allows the localization of a possible seizure onset zone (SOZ) during the interictal period. Stereo-electro-encephalography (SEEG) is the gold standard to define the SOZ. The objective of this research was to evaluate the accuracy of PET imaging in localizing the site of SOZ compared with SEEG. <b><i>Methods:</i></b> Seven patients with refractory tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The study baseline period consisted of a 3-month follow-up prior to electrode implantation. The study protocol for the baseline period included the following procedures: 1) obtaining an accurate description of seizure numbers and types in focal seizures without impaired awareness (focal aware seizures [FAS]), focal impaired awareness seizures (FIAS), and focal seizures evolving to generalized tonic-clonic seizures (GTCS); 2) EEG confirming paroxysmal activity in the temporal leads; 3) 1.5-T MRI oriented along the hippocampal axis for axial and coronal views confirming the presence of HS; 4) PET using 2-18 Ffluoro-2-deoxy-d-glucose ( 18 F-FDG) and 2′-18 F-fluoroflumazenil ( 18 F-FFMZ) as radiotracers for identification of SOZ through a quantitative voxel-by-voxel analysis; 13 5) neuropsychological evaluation, including language dominance, through use of the validated Spanish version of the dichotic listening test, 14 as well as a test battery to evaluate attention and memory (NEUROPSI), which has been validated in a Mexican population according to age and educational level and designed to avoid learning in subsequent examinations; 15 and 6) health-related quality of life assessed by the Quality of Life Epilepsy Inventory (QOLIE-89). 16,17…”
Section: Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…The study baseline period consisted of a 3-month follow-up prior to electrode implantation. The study protocol for the baseline period included the following procedures: 1) obtaining an accurate description of seizure numbers and types in focal seizures without impaired awareness (focal aware seizures [FAS]), focal impaired awareness seizures (FIAS), and focal seizures evolving to generalized tonic-clonic seizures (GTCS); 2) EEG confirming paroxysmal activity in the temporal leads; 3) 1.5-T MRI oriented along the hippocampal axis for axial and coronal views confirming the presence of HS; 4) PET using 2-18 Ffluoro-2-deoxy-d-glucose ( 18 F-FDG) and 2′-18 F-fluoroflumazenil ( 18 F-FFMZ) as radiotracers for identification of SOZ through a quantitative voxel-by-voxel analysis; 13 5) neuropsychological evaluation, including language dominance, through use of the validated Spanish version of the dichotic listening test, 14 as well as a test battery to evaluate attention and memory (NEUROPSI), which has been validated in a Mexican population according to age and educational level and designed to avoid learning in subsequent examinations; 15 and 6) health-related quality of life assessed by the Quality of Life Epilepsy Inventory (QOLIE-89). 16,17…”
Section: Baselinementioning
confidence: 99%
“…Preoperative PET-CT scans were acquired with 18 F-FDG and 18 F-FMZ radiotracers, searching the lowest radiotracer uptake region in the PHC to define the SOZ, as described previously. 13 On the day of surgery, MRI studies were fused to a CT scan performed with a stereotactic frame in place (Z-D Leibinger), and trajectories were planned through the use of 3A Praezis Plus software aiming to the SOZ in the PHC. Medtronic 3391 recordingstimulation electrodes, with four 3-mm contacts with a 7-mm center-to-center distance, were inserted using an occipital parasagittal burr hole and connected to a percutaneous extension for SEEG recording during subsequent days.…”
Section: Electrode Implantationmentioning
confidence: 99%
“…A study demonstrated that FDG-PET and FMZ-PET were able to identify SOZs by quantifying the reduced uptake/binding of FDG and FMZ radiopharmaceuticals. Moreover, the results matched 86% and 71% with the stereo-electro-encephalography (SEEG)-obtained data, which is considered the gold standard for localizing the seizure onset zone (SOZ) in the epileptic brain [ 137 ]. In another study, Q-PET analysis revealed that patients with juvenile myoclonic epilepsy (JME) showed reduced dopamine uptake due to hindered dopamine transporter activities [ 138 ].…”
Section: Recent Advancements In Diagnostic Techniquesmentioning
confidence: 69%
“…Figure 2 illustrates the target's size and location of the H, S, and PHC in the temporal lobe; we can appreciate that the size of PHC and location away from vascular structures represent an easier and safer surgical target to approach. One may argue that PHC is larger and, therefore, more difficult to determine the precise location of SOZ for electrodes' implantation; in this regard, the use of preoperative PET studies using a specific radiopharmaceutical tracer for GABA (18-FMZ), quantitative evaluation of its lowest uptake is highly sensitive to locate SOZ in the PHC ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the day of surgery, MRI studies were fused to a CT scan performed with a stereotactic frame in place (Z-D Leibinger, Freiburg, Germany), and trajectories were planned to use the 3A Plus Praezis software (Heidelberg, Germany), aiming at the targets (H, S, or PHC). Since the PHC was a larger target to perform SEEG and subsequent DBS, the electrode implantation for SEEG was guided by PET-CT scans, using the 18 Fluor-Flumazenil (18-FFMZ) as a radiotracer, where the area with the lowest uptake represents the area where the highest concentration of GABA ( 11 ). Anti-epileptic drugs (AEDs) were taken OFF during SEEG for the localization of SOZ.…”
Section: Electrode Implantation and Stimulation Parametersmentioning
confidence: 99%